2021
DOI: 10.4236/odem.2021.92006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Survivability of SARS-CoV-2 on Cardboard and Plastic Surfaces and the Transferability of Virus from Surface to Skin

Abstract: Objective: To 1) characterize the decay curve of infective SARS-CoV-2 over time on the surface of cardboard packaging and plastic mailer packaging; 2) characterize the transferability over time of virus-inoculated cardboard packaging and plastic mailer packaging to skin. Methods: We inoculated samples of plastic and cardboard packaging with a titer of SARS-CoV-2 > 10 6 TCID 50 / mL to evaluate the survivability and transferability to the skin (pig skin) over time. A cell culture-based infectivity assay (TCID 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…Our data on SARS-CoV-2 survival on surfaces are consistent with multiple research studies that showed that the half-life of SARS-CoV-2 at 20-27°C was between 1.5 and 9 hours in plastic surfaces 10,13,16,47 , and between 3.4 and 7.8 hours in stainless steel 9,13,16 . Nevertheless, other studies have shown a longer survival rate for SARS-CoV-2 on surfaces at similar temperatures, with half-lives in the order of days rather than hours 17,48 .…”
Section: Resultssupporting
confidence: 91%
“…Our data on SARS-CoV-2 survival on surfaces are consistent with multiple research studies that showed that the half-life of SARS-CoV-2 at 20-27°C was between 1.5 and 9 hours in plastic surfaces 10,13,16,47 , and between 3.4 and 7.8 hours in stainless steel 9,13,16 . Nevertheless, other studies have shown a longer survival rate for SARS-CoV-2 on surfaces at similar temperatures, with half-lives in the order of days rather than hours 17,48 .…”
Section: Resultssupporting
confidence: 91%
“…Our data on SARS-CoV-2 survival on surfaces are consistent with multiple research studies that showed that the half-life of SARS-CoV-2 at 20–27°C was between 1.5 and 9 hours in plastic surfaces ( 10 , 13 , 16 , 55 ), and between 3.4 and 7.8 hours in stainless steel ( 9 , 13 , 16 ). Nevertheless, other studies have shown a longer survival rate for SARS-CoV-2 on surfaces at similar temperatures, with half-lives in the order of days rather than hours ( 18 , 56 ).…”
Section: Resultssupporting
confidence: 90%
“…There are several ways by which a virus can spread, including corporal fluid particles through the air and over surfaces. Several studies with viruses, particularly coronaviruses, have indicated that plastic and polymeric surfaces allow for a higher half‐life of virus survival (Johnson et al, 2021). Hence, using suitable antiviral biobased materials in an active way (e.g., encapsulated for controlled release or as coatings) could help decrease the spread of viruses (Gonçalves et al, 2021; Lin et al, 2021; Marzoli et al, 2021).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%